How the dragon was tricked and other silly stories - Kelly, Miles (Miles Kelly Publishing Ltd Thaxted, 2013)
A marvellous selection of rib-tickling tales from authors such as Edward Lear and Rudyard Kipling. This book contains four hilarious stories and extracts that are all accompanied by superbly silly illustrations.